Programmatic and Administrative Barriers to High-Risk Infant Follow-Up Care - Tang, Brian G.; Lee, Henry C.; Gray, Erika E.; Gould, Jeffrey B.; Hintz, Susan R. (American Journal of Perinatology, 2018)
Objective This article characterizes programmatic features of a population-based network of high-risk infant follow-up programs and identifies potential challenges associated with attendance from the providers' perspective.Study Design A web-based survey of high-risk infant follow-up program directors, coordinators, and providers of a statewide high-risk infant follow-up system. Frequencies and percentages were used to describe the survey responses.Results Of the 68 high-risk infant follow-up programs in California, 56 (82%) responded to the survey. The first visit no-show rate between 10 and 30% was estimated by 44% of programs with higher no-show rates for subsequent visits. Common strategies to remind families of appointments were phone calls and mailings. Most programs (54%) did not have a strategy to help families who lived distant to the high-risk infant follow-up clinic.Conclusion High-risk infant follow-up programs may lack resources and effective strategies to enhance follow-up, particularly for those living at a distance.
Keywords: preterm infants; health services; neonatal follow-up; high-risk infants